Gaya Lateral Ekuivalen SNI 1726:2019 Untuk Perbandingan ETABS dan SAP 2000: - Tiara Effani; Hafiz Hamdani; Maya Saridewi Pascanawaty; Ahmad Zarkas (Institut Teknologi Garut, 2026)
Indonesia has a high level of earthquake risk due to the interaction of active tectonic plates. This condition requires structural building planning that strictly complies with earthquake-resistant design regulations. This study aims to analyze the structural response of buildings to earthquake loads using the equivalent lateral force method based on SNI 1726:2019. The research also aims to conduct simulation and static analysis of a two-story building structure using ETABS and SAP2000 software in order to compare the results of inter-story drift, base shear calculations, and structural responses to earthquake loads. The comparison of the two software programs is intended to help verify whether the outputs, such as inter-story drift and base shear, show consistent patterns.The research method was carried out through three-dimensional structural modeling using the same parameters in both ETABS and SAP2000. Earthquake loading was calculated using the equivalent lateral force method. The results show that both software programs produce similar earthquake force distribution patterns; however, there are differences in the values of inter-story drift and base shear. The maximum inter-story drift produced by SAP2000 was 0.018055 m, while the maximum drift produced by ETABS was 0.014685 m. This indicates that SAP2000 generated a larger inter-story drift value compared to ETABS, with a percentage difference of 0.86%. Meanwhile, for the base shear values, both software programs also showed differences, where SAP2000 produced a base shear of 1753.734 kN, while ETABS produced a base shear of 1841.7433 kN. In this case, ETABS generated a larger base shear value compared to SAP2000, with a percentage difference of 0.95%. These differences are influenced by numerical assumptions and analysis parameter settings in each application. In general, the analysis results are still within the tolerance limits permitted by the standards.